Evaluation of The Implementation of Environmental Management System Based on ISO 14001:2015 at PT X, Batam City - Fauzi, Asnil; Nur Jading, Rasmin; Jamal, Jamal (Rifa'Institute, 2025)
In the era of globalization, industrial and business activities significantly contribute to environmental impacts, making systematic environmental management crucial. This study analyzes the implementation of an Environmental Management System (EMS) at PT “X” based on ISO 14001:2015, evaluates its performance, and identifies its impact on environmental sustainability. A qualitative approach was employed, with data collected through in-depth interviews, field observations, and document analysis. Informants consisted of five representatives from key functional areas, including top management, accounting, HSES (Health, Safety, Environment & Security), and Quality Assurance as the internal auditor. The interview guidelines were designed according to ISO 14001:2015 clauses to ensure comprehensive coverage. The findings indicate strong top management commitment in supporting EMS implementation through policies that encompass planning, execution, and monitoring. The organizational structure effectively facilitates the environmental management cycle, including identifying, addressing, and resolving findings categorized as major non-conformities, minor non-conformities, and opportunities for improvement. These serve as the basis for performance evaluation and continuous improvement. In conclusion, PT “X” has effectively implemented EMS in line with ISO 14001:2015 and complies with Indonesia’s Law No. 32/2009 on Environmental Protection and Management. The company demonstrates environmental responsibility, and continuous improvement is recommended to strengthen sustainability and stakeholder trust.